A Generalized Singular Value Decomposition Strategy for Estimating the Block Recursive Simultaneous Equations Model - Cosbuc, Mircea I.; Gatu, Cristian; Colubi, Ana; Kontoghiorghes, Erricos John (My University, 2017)
A new strategy for deriving the three-stage least squares (3SLS) estimator of the simultaneous equations model (SEM) is proposed. The main numerical tool employed is the generalized singular value decomposition. This provides a numerical estimation procedure which can tackle efficiently the particular case when the variance-covariance matrix is singular. The proposed algorithm is further adapted to deal with the special case of the block-recursive SEM. The block diagonal structure of the variance-covariance matrix is exploited in order to reduce significantly the computational burden. Experimental results are presented to illustrate the computational efficiency of the new estimation strategy when compared with the equivalent method that ignores the block-recursive structure of the SEM.
Keywords: Block recursive SEM; Three-stage least squares; Generalized SVD